(untitled) - Grisham, John (New York, New York, 2015)
"Theo thought the danger had passed, but he's about to face off against an old adversary: accused murderer and fugitive Pete Duffy. On a field trip to Washington, DC, Theo spots a familiar face on the Metro: Duffy, who jumped bail and was never seen again. Theo's quick thinking helps bring Duffy back to Strattenburg to stand trial. But now that Duffy knows who he is, Theo is in greater danger than he's ever been in before"--Dust jacket flap.
Keywords: Fiction; Fugitives from justice; Fiction; School field trips; Fiction; Lawyers; School field trips; Fugitives from justice; Juvenile fiction; Juvenile fiction; Lawyers; Legal stories; Juvenile fiction